(3GdeHYK hGdeZGRis - (3ESeGYjd Hf eMeO Hf GdaVd Hf Ydj GdbQTj CHh GdbGSe GdWdjMj GdJejej, bhGe GdSfI,J (B535 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG JMUi fYeg , hdG jHdZ cfg TcQg s
(3BNQgG (B:s
(3BNQ cJGH GdeHYK hGdeZGRi GdJi UfagG LOi GdZeGe GdMGaX dcGJHg SHW Gdeedi jMji Hf eMeO Hf SYO Gdecfi HCHi GdaQL s
(3hHGdUaMI GdCNjQI eWGdYI GdCMeO Hf jMji Hf eMeO Hf YeQ GdTgQRhOi eDQNI SfI (B725(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B323 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B126 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(1138) s
Keywords: (3GdJGQjNs